A política comercial brasileira e as barreiras impostas às exportações de carne de frango: uma aplicação do método MicMac - Leite Filho, Arceste (2016)
The main objective of this paper was to analyze tariff and non-tariff barriers on the international trade of chicken meat, and its possible impact on world trade. As secondary objectives, the main problems affecting the competitive capacity of the Brazilian poultry sector were analyzed, and afterwards the main barriers that impede poultry trade were analyzed. The survey of the secondary objectives was carried out through bibliographical research in the main government agencies and research institutes on the subject. For the analysis of the research, the MICMAC Method was used, based on interviews with the managers of the main chicken meat producing industries of the western region of Paraná. The results obtained showed the fragile points of the Brazilian export system and indicated where the actions should be taken by the state in order to redress or minimize the harmful effects of these barriers. In this context, the study was justified by the importance and relevance of the topic, presenting important regulations for Brazilian exports.